1995
DOI: 10.1038/ki.1995.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes and peritonitis on the peritoneal equilibration test

Abstract: Peritoneal equilibration tests (PET) were performed on 47 patients (15 diabetics) who had been on CAPD for 1 to 112 months. Among new patients on CAPD (1 to 3 months) with no history of peritonitis, diabetics had higher D/PCr than non-diabetics (P < 0.02). However, after > or = 7 months of CAPD, in patients with < or = 2 episodes of peritonitis, glucose and creatinine transport rates were lower (P < 0.05) in diabetic than non-diabetic patients. Among patients on CAPD for > or = 7 months, creatinine (P < 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 13 publications
2
30
1
Order By: Relevance
“…In peritoneal dialysis, hypertonic glucose dialysates raise the osmolality in excess of the capillary, which creates the main initial driving force of ultrafiltration. Earlier reports have suggested that hyperglycemia in diabetic patients can lead to reduced PET ultrafiltration volumes (16). Despite our diabetic patients having a greater D4/Pcreatinine ratio than the nondiabetic patients, in keeping with other reports (6) we found no association between PET net ultrafiltration volumes and either blood glucose or hemoglobin A1c measurements.…”
Section: Discussionsupporting
confidence: 74%
“…In peritoneal dialysis, hypertonic glucose dialysates raise the osmolality in excess of the capillary, which creates the main initial driving force of ultrafiltration. Earlier reports have suggested that hyperglycemia in diabetic patients can lead to reduced PET ultrafiltration volumes (16). Despite our diabetic patients having a greater D4/Pcreatinine ratio than the nondiabetic patients, in keeping with other reports (6) we found no association between PET net ultrafiltration volumes and either blood glucose or hemoglobin A1c measurements.…”
Section: Discussionsupporting
confidence: 74%
“…We did observe that female diabetic patients, but not males, had an increased PET D4/P creatinine, but no differences in D4/D0 glucose or PET net ultrafiltration volume, in keeping with more recent studies [21]. In addition, there was no difference in peritoneal glucose absorption in the diabetics compared to the nondiabetics.…”
Section: Discussionsupporting
confidence: 73%
“…However, glucose absorption was not increased in the diabetic groups, despite the diabetic patients having increased random blood glucose and HbA1c values. Previous studies have suggested that the higher blood sugar levels in diabetic patients could lead to reduced net ultrafiltration by reducing the peritoneal to blood glucose osmotic gradient, with consequent increased reliance on peritoneal dialysis solutions with higher glucose content [21]. However, these earlier studies were typically performed in patients using standard glucose-based dialysates, rather than in patients using icodextrin.…”
Section: Discussionmentioning
confidence: 85%
“…17 There are also complications derived from fluid overload since diabetes has long been associated with high peritoneal transport, which reduces fluid removal. 18,19 In the last decade, icodextrin was introduced in Europe as an osmotic agent in PD solutions. 20,21 Icodextrin has an advantage over glucose in the maintenance of the osmotic gradient for a longer time, making ultrafiltration more efficient and thus reducing overhydration, hypertension, and left ventricular hypertrophy.…”
mentioning
confidence: 99%